HOXA13, Negatively Regulated by miR-139-5p, Decreases the Sensitivity of Gastric Cancer to 5-Fluorouracil Possibly by Targeting ABCC4 - Chen, Zhengqian; Qin, Zhiwei; Li, Lei; Wo, Qi; Chen, Xia (Frontiers in Oncology, 2021)
Purpose Chemoresistance remains a major challenge in the therapy of gastric cancer (GC). The homeobox (HOX) gene family has gained attention in carcinogenesis and chemoresistance. Here, this study aimed to explore the mechanism of HOXA13 in GC chemoresistance. Methods Quantitative real-time PCR (qRT-PCR) and Western blot were used to evaluate the expression of HOXA13 in GC tissues. The Kaplan-Meier plotter database was mined for prognosis analysis of GC patients with different HOXA13 expression receiving 5-Fluorouracil (5-FU) therapy. The effects of HOXA13 on sensitivity of GC cells to 5-FU were investigated by Cell Counting Kit-8 (CCK-8), 5-Ethynyl-2’-deoxyuridine (EdU) incorporation, flow cytometry and experiment in vivo. RNA-Sequencing analysis was performed to explore the underlying mechanism of HOXA13-meidiated 5-FU resistance in GC. Chromatin immunoprecipitation (ChIP) and rescue experiments were applied to determine the relationship between HOXA13 and ABCC4. Luciferase reporter assay was performed to assess interaction of miR-139-5p and HOXA13. Results HOXA13 was upregulated in GC and its high expression was associated with poor prognosis of GC patients with 5-FU treatment. Overexpression of HOXA13 impaired the inhibitory effects of 5-FU on GC cells proliferation in vitro and vivo, and knockdown of HOXA13 exacerbated 5-FU-induced GC cells apoptosis. Mechanistically, HOXA13, directly targeted by miR-139-5p in GC, might upregulate ABCC4 expression, thereby accentuating 5-FU resistance of GC cells. Conclusion Our study suggests that HOXA13 attenuates 5-FU sensitivity of GC possibly by upregulating ABCC4. Thus, targeting HOXA13 would provide a novel prospective into the potential therapeutic strategy for reversing chemoresistance.